2017
DOI: 10.1111/dme.13516
|View full text |Cite
|
Sign up to set email alerts
|

High risk of conversion to diabetes in first-degree relatives of individuals with young-onset type 2 diabetes: a 12-year follow-up analysis

Abstract: First-degree relatives of people with Type 2 diabetes, especially relatives of those with young-onset diabetes, are at high risk for diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…They had undergone the same detailed clinical and metabolic evaluation as women with PCOS, including a standard 75-g oral glucose tolerance test (OGTT) at baseline. All women without PCOS were recalled for follow-up metabolic evaluation, including OGTT, approximately 10 years after the initial visit [12]. Participants with hypothyroidism, prolactinoma, nonclassical adrenal hyperplasia, or Cushing’s syndrome were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…They had undergone the same detailed clinical and metabolic evaluation as women with PCOS, including a standard 75-g oral glucose tolerance test (OGTT) at baseline. All women without PCOS were recalled for follow-up metabolic evaluation, including OGTT, approximately 10 years after the initial visit [12]. Participants with hypothyroidism, prolactinoma, nonclassical adrenal hyperplasia, or Cushing’s syndrome were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, study found that in individuals with a family history of young-onset, over 20% of siblings with an average age of 40 years had diabetes and 25% had prediabetes. After a decade, over one-fifth of those who were initially euglycaemic had developed Type 2 diabetes [16]. Previous studies have demonstrated that continuous glucose monitoring could identify the presence of significant dysglycaemia in FDR who were categorized as having normal glucose tolerance according to the OGTT [17].…”
Section: Discussionmentioning
confidence: 99%
“…(41) Factors other than weight status are known to increase risk of diabetes, including minority race/ethnicity and family history of diabetes. (7, 41–43) Indeed, due to their relevance, these factors are included in the pediatric screening guideline that we evaluated in our study. There are likely other factors that impact diabetes risk that are yet to be discovered.…”
Section: Discussionmentioning
confidence: 99%